Feasibility Study of Hybrid Photovoltaic (PV)-Generator Set Power Plant at Palm Oil Mill - Saputra, Ramadian; Jelita, Marhama (PROtek : Jurnal Ilmiah Teknik Elektro, 2025)
Kuko Palm Oil Mill, currently not interconnected with PLN electricity, relies on diesel-fueled generators of 1100 kVA and 650 kVA to meet its electrical needs. To reduce diesel consumption, a Hybrid Power Plant (PLTH) system comprising generators, batteries, and Photovoltaic (PV) panels is proposed. Optimization studies, evaluating technical and economic feasibility, are conducted using HOMER software. Optimal PLTH configuration includes 8,727 kW PV, 500 kW generator, 1,000 kW generator, 25,708 battery units, and 1,481 kW converter. PLTH generates 14,339,116 kWh/year, fulfilling PKS electricity requirements. Economic analysis yields NPC of Rp356,000,000,000, initial investment of Rp77,400,000,000, operation and maintenance costs of Rp21,600,000,000, and LCOE of Rp3,147/kWh. IRR stands at 22%, NPV is positive at Rp124,000,000,000, with a 3.5-year capital return. These results indicate PLTH feasibility both technically and economically